Beginning WF Windows Workflow in .NET 4.0 - Collins, Mark J.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Windows Workflow Foundation is a ground-breaking addition to the core of the .NET Framework that allows you to orchestrate human and system interactions as a series of workflows that can be easily mapped, analyzed, adjusted, and implemented. As business problems become more complex, the need for a workflow-based solution has never been more evident. WF provides a simple and consistent way to model and implement complex problems. As a developer, you focus on developing the business logic for individual workflow tasks. The runtime handles the execution of those tasks after they have been composed into a workflow. Beginning WF demonstrates, in an eminently readable and accessible style, how Microsoft's Workflow Foundation (WF) technology can be used in a wide variety of applications. Loaded with lots of simple yet demonstrative sample projects Very hands-on with practical "how-to" information Indexed by feature so specific questions are easily answered
Building a Simple Workflow -- Coded Workflows -- Flowchart Workflow -- Designing Workflows -- Passing Arguments -- Replicated Activities -- Exception Handling -- Extending the Built-In Activities -- Communication -- Send and Receive -- Communicating with the Host Application -- Web Services -- Workflow Extensions -- SQL Persistence -- Extensions -- Tracking -- Transactions -- Transactions with Persistence -- WorkflowServiceHost -- Advanced Topics -- Compensation, Confirmation, and Cancellation -- Collections -- Interoperability with Workflow 3.5 -- Policy.
Keywords: Computer science; Computer Science; Programming Languages, Compilers, Interpreters